The Role of Prosthetics in The Treatment of Diseases of The Maxillofacial Region (Eurasian Scientific Herald, 2022)
Reasons for the high need for orthopedic treatment with removable dentures, the leading position is still occupied by " insufficient sanitation of the oral cavity, untimely access of patients to the dentist." In addition, an important role is played by the problem of imperfection of materials and technologies used for the manufacture of dentures, leading to deterioration of the dental system [1.3.5.7.9]. Time lag is a sliding body that undergoes the process of crushing chains and crushing food blocks, in other colas it is a multi-layered galaxy that grinds its teeth with anger and rage. NPZHB - complex and coordinated, according to the description of movements, the hinges are locking [1.3.5].